The History of MDMA as an Underground Drug in the United States, 1960–1979. Issue 2 (14th March 2016) - Passie, Torsten; Benzenhöfer, Udo
ABSTRACT: MDMA (3, 4-methylenedioxy-methylamphetamine, a.k.a. "ecstasy") was first synthesized in 1912 and resynthesized more than once for pharmaceutical reasons before it became a popular recreational drug. Partially based on previously overlooked U.S. government documentation, this article reconstructs the early history of MDMA as a recreational drug in the U.S. from 1960 to 1979. According to the literature, MDMA was introduced as a street drug at the end of the 1960s. The first forensic detection of MDMA "on the street" was reported in 1970 in Chicago. It appears that MDMA was first synthesized by underground chemists in search of "legal alternatives" for the closely related and highly sought-after drug MDA, which was scheduled under the Controlled Substances Act (CSA) in 1970. Until 1974, nearly all MDMA street samples seized came from the U.S. Midwest, the first "hot region" of MDMA use. In Canada, MDMA was first detected in 1974 and scheduled in 1976. From 1975 to 1979, MDMA was found in street samples in more than 10 U.S. states, the West Coast becoming the major "hot region" of MDMA use. Recreational use of MDMA spread across the U.S. in the early 1980s, and in 1985 it was scheduled under the CSA.